Inceasing isopropanol tolerance in escherichia coli using randomized libraries of camp receptor protein - Lim, Therese Shi Min. (2010)
Depletion of natural energy resources and global climate change has renewed much interest in biofuels as an alternative form of energy. Isopropanol is both a desired fuel and essential chemical feedstock in the petrochemical industry. It is produced from fermentation using biocatalysts. Here in this work, we used directed evolution method to mutate the global transcription factor, cAMP Receptor Protein (CRP), to engineer isopropanol tolerance in Escherichia Coli (E. Coli). This has significant importance in increasing cell growth in high isopropanol concentrations and hence improving industrial production of isopropanol. In this study, a total of 3 different mutants were obtained. Each of the mutants has at least one mutation site adjacent to or inside the cAMP/ DNA binding pocket of the CRP protein. Also, all mutants were able to achieve about twice or more cell number concentrations than the wild-type cells. However, it was noted that the mutants have got shorter life spans due to shorter lag and exponential growth phases.